The Influence of Product Quality, Service Quality, and Location on Customer Loyalty at Depot Wakik Gresik - Rahmah Renanda Fantika; J.E. Sutanto; Moses Soediro; Adrie Oktavio (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research entitled